Evaluation of the effects of Occlusal Stabilization Appliance on the cervical dystonia symptoms - Borhani, Nasim; salari, mehri; Ashrafi, Farzad; Kolivand, Soodabeh (Student Research in Translational Medicine, 2023)
Background and aims: Cervical dystonia is a contraction of the neck muscles that causes movement problems, pain, and dysfunction in daily functioning. This problem can occur for a variety of reasons, and today it is more common due to computer work or working with mobile phones (any factor that causes prolonged pressure on the neck). Occlusal Stabilization Appliance (OSA) is a dental splint that is said that it is a good method to relax neck and face muscles, reduce symptoms, and even relieve cervical dystonia. In this study, we aimed to investigate the effects of OSA in reducing patient’s symptoms. Methods: In this experimental study performed on patients with cervical dystonia referred to Shohada-e-Tajrish Hospital from start to the end of 2019, 7 patients were studied. OSA was created for patients and the patients were followed up 24 hours, 3 months after using OSA. Follow-ups were performed using the Dystonia Assessment Questionnaire (TWSTRS) and dystonia scaling and examination for improvement. Results: Three patients were male and four were female. The mean age was 42 ± 11.66 years. Patients had a mean history of dystonia of 10±8 years. There was no statistically significant difference between total relaxation, pain reduction, increased sleep quality, and tremor disappearance between 24 hours and 3 months after prosthesis, but there was a statistically significant difference in increased comfort 24 hours and 3 months after prosthesis (P-value = 0.053). Using OSA improves Rotation, Duration, and Maintain head max time. Conclusion: The use of OSA in the short term improves pain, increases the quality of sleep, relaxation, and elimination of tremor, but in the long term, has no effect on reducing these parameters.